On the creation of the information logistic system of universities based on cloud technology - K. I. Halasun; Y. V. Y. V. Tryus (Academy of Cognitive and Natural Sciences, 2013)
The declaration "Education for Innovative Societies in the 21st Century", adopted at the G8 Summit in St. Petersburg in 2006, states the unsatisfactory state of education in the world. The declaration proposes measures for the universalization of education systems, the formation of a global innovation society, increasing international academic mobility, the development of life and work skills, and creating a unified global information network. In general, it should be noted that not much progress has been made in the field of education reform so far, and the main problem is that the declared goals are not supported by a workable mechanism for their implementation. In the field of economics and business, such a universal mechanism is logistics.